Pengaruh Intellectual Capital, Konservatisme Akuntansi dan Investment Opportunity Set Terhadap Kualitas Laba - Trias Fajrin Prihatini; Suwarno Suwarno (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to test intellectual capital, accounting conservatism, and invenstment opportunity set on earnings quality. The data source used in this research is secondary data using documentasy data obtained from the official website of the Indonesian Stock Exchange. The sample used in this research was 28 data from consumer goods industrial companies in 2020-2022 using purposive sampling. This research uses multiple linear regression analysis techniques. The regression results show that intellectual capital has a negative effect on earnings quality and aacounting conservatism has a positive effect on earnings quality, while investment opportunity set has no effect on earnings quality.